PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA DAN DIGITAL MARKETING TERHADAP KEPUASAN PELANGGAN KAPTUR BARBERSHOP CIBODAS KOTA TANGERANG - Sukma Wijaya, Muhamad; Syah, Hidayat; Mardiany Djaenudin, Ernie (Desanta Publisher, 2025)
This research aims to determine the partial influence of service quality, price perception, and digital marketing on customer satisfaction at Kaptur Barbershop Cibodas, Tangerang City. In collecting this data, it was obtained using primary data and distributing questionnaires. The population in this study were consumers who had shaved their hair at Kaptur Barbershop in Cibodas, Tangerang City, with a sample of 100 respondents. This research uses a quantitative research method with a non-probability sampling technique, namely the incidental sampling method, and uses an analysis model technique with the Partial Least Square method with the Structural Equation Modeling (PLS-SEM) type of modeling, processed using the SmartPLS version 3.0 program. The results of this research show that the variables of service quality, price perception, and digital marketing directly have a positive and significant effect on customer satisfaction at Kaptur Barbershop.